Women of Ait Bouguemez: How Tourism Affects Identities - Wafaa Tizza (Via@)
Since the recent changes in the status of women in Morroco, gender has become a widely debated issue, both on the national and on the local level. In the case of fringe areas such as the valley of Ait Bouguemez, the involvement of women in local development projects initiated by the state or by NGOs through ACF (Women’s Associations and Cooperatives) has demonstrated great capacities for their empowerment. Through this fact, new women’s groups have emerged with a forward-looking vision and a new view of their local heritage which reinforces identity representations. Despite women’s low income, social-cultural constraints and the alignement of ACF on institutions, it appears that these ACF have nevertheless strongly contributed to the reformulation of new female identities in rural settings.